Youth homelessness: a review of social programs - Wilton, Lori (My University, 2019)
Youth homelessness is a complex problem in Canada. While social programs do exist to help homeless youth, there appears to be some confusion as to which program is best suited for helping homeless youth be successful in their lives. This paper examines how social programs help youth leave the streets. The paper analyzes three levels of social programs starting with informal programs, middle-mode programs and formal programs in an attempt to determine the best way to reintegrate homeless youth back into mainstream society. A close examination of social programs suggests that more funding is needed to provide more spaces for youth participation as well as emotional supports to provide stability in their lives. Currently, there are gaps between the social programs. Each program has its own individual rules for operation and does not adequately support transitioning youth. Youth homelessness occurs due to the breakdown of the micro, meso and macro level institutions leaving youth to attempt to take control of their own lives by living homeless.